Emotional intelligence and academic achievement in students of the professional school of accountancy from "Señor de Sipan" University - Rosas Prado, Carmen Elvira (2015)
This research arose from the need to determine the degree of relationship between two complex constructs in academic education of students in school Accounting, emotional intelligence and academic performance. The scientific theoretical basis of emotional intelligence is based on the theory of Reuven Bar-On, which built the Emotional Quotient Inventory (I-CE), whose systemic model considers five conceptual components, involving 15 factors (sub) under a factorial structure. The methodology is based on a quantitative approach, whose design is not experimental transactional correlational, so the research hypotheses were bivariate and multivariate causal. The sample consisted of 300 male and female students from I to X cycle. The correlation analysis between the different components of emotional intelligence and academic performance, show that for the intrapersonal component (CIA), adaptability (CAD) and stress management (CME), there is a significant correlation at the 0.01 level, in exchange for the component general mood (CAG), the correlation was significant at the 0.05 level. It should be noted that all the correlations were low. As regards the analysis of correlation between emotional quotient and overall academic performance, Pearson correlation coefficient r = 0.204 showed a **, significant value at a level 0.01.